Improvement of Cellularity on Cell Block Preparations Using the So-Called Tissue Coagulum Clot Method During Endobronchial Ultrasound-Guided Transbronchial Fine-Needle Aspiration - Yung, Rex Chin Wei (Cancer Cytopathol, 2011)
BACKGROUND: Cell block (CB) preparation during the endobronchial ultrasound-guided transbronchial fine-needle aspiration (EBUS-TBNA) procedure plays an important role in the diagnosis of lung cancer and recovery of cellular material for molecular characterization of the tumor. However, the efficiency of the conventional method of CB preparation is suboptimal. METHODS: In the current study, the “tissue coagulum clot” cell block (TCC-CB) method was used to prepare the CBs and its efficiency was compared with that of the conventional saline rinse cell block (NR-CB) method. A total of 84 consecutive TCC-CBs (106 lymph nodes [LNs] and 14 lung lesions) and 28 consecutive cases of NR-CB (39 LNs and 3 lung lesions) obtained within the same time period were included in the current study. RESULTS: In the TCC-CB specimens, 94 of 106 LN cases (88.7%) yielded sufficient diagnostic material, as did 11 of 14 lung lesions (78.6%). In the NR-CB group, which was used as the control, 22 of 39 LN specimens (56.4%) and none of 3 lung specimens (0%) were found to provide sufficient diagnostic material. Although the average size of the LNs in the study group were not significantly different from those in the control group (1.76 cm vs 1.82 cm; P>.05), the overall nondiagnostic rates in the TCC-CB and NR-CB groups were 11.2% and 43.6%, respectively (P<.001). The nondiagnostic rates of the lung specimens were 15.4% in the TCC-CB group and 100% in the NR-CB group (P<.05). In addition, immunohistochemistry studies and epidermal growth factor receptor (EGFR)/KRAS mutational analyses were performed in 26 and 14 TCC-CB cases, respectively. With the exception of 1 case, all of them had satisfactory results. CONCLUSIONS: The data from the current study demonstrate that the TCC-CB method significantly increases the cellular yield of CB preparations without compromising cytomorphological characterization of tumor cells.